Regioselective synthesis of benzo[b]indeno[1, 2-e][1, 4]thiazin-11(10aH)-ones and antimicrobial evaluation thereof. Issue 13 (18th July 2022) - Mor, Satbir; Khatri, Mohini
Abstract: Benzo[ b ]indeno[1, 2- e ][1, 4]thiazin-11(10 aH )-ones 8a –h were synthesized regioselectively via cyclocondensation of 2, 5-dibromo-2-(substitutedphenyl)-1 H -indene-1, 3(2 H )-diones 4a –c and 2-aminobenzenethiols 7a –e using freshly dried EtOH as solvent with 42–60% yields. The synthesized derivatives were well-characterized by employing different spectral techniques (FTIR, 1 H and 13 C NMR, and HRMS) and X-ray crystallographic analysis. All the derivatives were examined for their preliminary in vitro antimicrobial activity against two Gram-positive bacterial strains, i.e., Bacillus subtilis, and Staphylococcus aureus, two Gram-negative bacterial strains, i.e., Pseudomonas aeruginosa and Escherichia coli, and two fungal strains, i.e., Candida albicans and Rhizopus oryzae employing serial dilution method taking Ciprofloxacin and Fluconazole as standard reference drugs for antibacterial and antifungal activities, respectively. Among all the tested derivatives, 8h was found to exhibit significant inhibition against all the microbial strains under study. Graphical Abstract: UF0001